High civil service changing analyse's : a contribution to the study of State reform's in Mali - (:unkn) unknown (My University, 2014)
The winds of democratization that swept early 90s in most African countries, has resulted in significant changes in the political, social and administrative. Among the concerns listed on the political agenda of the time included the institutional reforms, including those of the State and its agencies. This was due to the deeply degraded nature and characterized further characterizes the relationship between the state and society. Also, this result it is, most often directly from the weak state apparatus and deficiencies of organization and ensuing management. Because of the filial relationship between senior public and the state, a reform that could help the other. It should however be noted that the senior civil service is a sphere of the state, so it does not represent that the administrative state. Therefore, it must act in close cooperation with the political state and social bodies. To do this, is needed both a root of the institution in its traditional values and openness to certain values of the new public management.
Keywords: African Research